Giant Dissecting Aortic Aneurysm in an Asymptomatic Young Male - Priyank Shah; Nishant Gupta; Irvin Goldfarb; Fayez Shamoon (Case Reports in Vascular Medicine)
Giant aortic aneurysm is defined as aneurysm in the aorta greater than 10 cm in diameter. It is a rare finding since most patients will present with complications of dissection or rupture before the size of aneurysm reaches that magnitude. Etiological factors include atherosclerosis, Marfan’s syndrome, giant cell arteritis, tuberculosis, syphilis, HIV-associated vasculitis, hereditary hemorrhagic telangiectasia, and medial agenesis. Once diagnosed, prompt surgical intervention is the treatment of choice. Although asymptomatic unruptured giant aortic aneurysm has been reported in the literature, there has not been any case of asymptomatic giant dissecting aortic aneurysm reported in the literature thus far. We report a case of giant dissecting ascending aortic aneurysm in an asymptomatic young male who was referred to our institution for abnormal findings on physical exam.